فعالية السياسة النقدية في ضبط متغيرات المربع السحري لكالدور في الجزائر (2000ـ 2020). - بوشنب, موسى (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى تحديد أثر السياسة النقدية على متغيرات المربع السحري لكالدور و إبراز مدى مساهمتها في ضبط تلك المتغيرات في الجزائر خلال الفترة (2000 ــ 2020). وخلصت الدراسة إلى العديد من النتائج أهمها أن السياسة النقدية في الجزائر خلال الفترة (2000 ــ2020) كانت فعالة في تحقيق هدف الاستقرار في المستوى العام للأسعار في حين بقيت عاجزة عن تحقيق هدف الرفع من معدل النمو الاقتصادي، تخفيض معدلات البطالة وتحقيق التوازن في ميزان المدفوعات، والتي تبقى مرتبطة بتغيرات الوضع الدولي ولا سيما تقلبات أسعار البترول في الأسواق العالمية. The aim of this study is to determinethe effects monetary policy on the Kaldor magic square variables, as wellas to highlight theextent to which itcontributes to thecontrol ofthesevariables in Algeria duringthe period (2000-2020). Thestudyconcluded with manyresults, the most important of them is that the monetary policy in algeria during the period (2000-2020) was onlyEffectivein reachingthegoalof stabilityin thegeneral, pricelevel, whileit remained unableto achievethegoal of raisingtherate ofeconomicgrowth, reducing unemployment ratesand a hieving, balance of payments, which remains linked to changes in the international situation, especiallythe fluctuations in oil prices in world markets.
Theeffectiveness of monetary policyin controlling thevariables of the kaldor magic square in Algeria(2000-2020)
مقال
Keywords: السياسة النقدية ; المربع السحري لكالدور ; النمو الاقتصادي ; التضخم ; ميزان المدفوعات